Communication Pattern of Dietary Intervention for Autism Spectrum Disorder Children on Facebook - Oktaviana Purnamasari (ETTISAL : Journal of Communication, 2022)
AbstractAutism Spectrum Disorder (ASD) children need appropriate treatment and intervention as early as possible after the diagnosis was made. Besides therapy, diet is one of the interventions that could be carried out by parents, although the positive effects of diet are still debatable among experts. This study aimed to understand the pattern of seeking information related to dietary interventions for ASD children in a virtual community of parent support group in Indonesia. The data was obtained from a virtual community on Facebook, named LRD Member Suar Autisme. This research was qualitative with virtual ethnographic method. The data collection technique was carried out through participant observation on the LRD Member Suar Autisme Facebook account, by examining 178 uploads, 3,569 comments and interview with community members. The results showed that the pattern of seeking information about dietary interventions by community members began with questions or seeking information regarding certain matters. In addition, it can also be identified patterns of presenting information about dietary intervention by admins. Our study showed that dietary intervention was one of the ways suggested by the community to reduce the improper behaviour of ASD children, especially based on the experiences of admins and members in the virtual community